2006
DOI: 10.1002/hed.20433
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype–genotype correlation: Challenge of intestinal-type adenocarcinoma of the nasal cavity and paranasal sinuses

Abstract: Our data confirm the phenotypic similarities at the genetic level between colorectal cancer and ITACs showing deregulation of K-Ras/BRAF and loss of heterozygosity (LOH) of chromosome 18q. By contrast, both frequency rate and type of inactivation of the APC-beta-catenin pathway differ in the 2 tumors, suggesting different gatekeeper events in the early development of ITAC (p16(INK4a) and TP53) and colorectal cancer (APC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
35
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 22 publications
4
35
1
Order By: Relevance
“…Our data are consistent with previous studies demonstrating that ITACs share genetic similarities with microsatellite stable colorectal cancers [32,33]. Until now, the involvement of APC in ITACs has been poorly examined.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data are consistent with previous studies demonstrating that ITACs share genetic similarities with microsatellite stable colorectal cancers [32,33]. Until now, the involvement of APC in ITACs has been poorly examined.…”
Section: Discussionsupporting
confidence: 93%
“…Until now, the involvement of APC in ITACs has been poorly examined. To our knowledge, a single mutational study of the gene has been performed, reporting only missense mutations, which might not affect the APC protein activity [32]. In this study, we demonstrated a concurrent hypermethylation and allelic loss of APC that determined lack of protein expression in the neuroendocrine component.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…11 Further attempts to find genetic alterations as described in colorectal adenocarcinoma concerned APC, b-catenin, and various mismatch repair genes gave negative results. 10,15,17 These results indicate that ITAC and colorectal adenocarcinoma have different genetic pathways of development and progression.…”
mentioning
confidence: 90%
“…2,3,5 Little is known about genetic alterations in human sinonasal cancer, published findings being based on a relatively limited number of cases and mostly involving adenocarcinoma tumors; the adenocarcinomas have often been those from an ethmoidal location or classified as of intestinal type. In these studies, high frequencies of DNA copy number changes as detected by comparative genomic hybridization have been detected, 17,18 whereas mutation rates reported for the KRAS gene [19][20][21][22][23][24] and the TP53 tumor suppressor gene have been lower. 23,[25][26][27] This study sought to clarify whether mutational mechanisms are involved in sinonasal carcinogenesis and their relation to wood-dust exposure.…”
mentioning
confidence: 99%